Obravnava bolnika z bolečino v križu - Drobnič-Kovač, Doroteja (Zdravniški vestnik, 2002)
Background. Low back pain is one of the most frequent reasons for consulting general practitioner. Little is known about etiology and pathogenesis of low back pain. General practitioner use different methods for the treatment of patients with low back pain. The choice of kind of therapy is not related withthe used diagnostic method. A large variety of therapeutic interventions is available for treatment of low back pain, but the effectiveness of most of them has not been demonstrated. The treatment of low back pain is mainly conservative and symptomatic. Conclusions. In the article are reviewed and critically evaluated different diagnostic and therapeutic methods used by physicians for the treatment of patients with low back pain. Results of existing studies suggest that applied therapeutic treatments mainly do not base on scientific based results.
Keywords: Absenteeism; Absentizem; bolečina; Bolečina v križu; Diagnosis; diagnostika; hrbtenica; križ; Low back pain; potek; Primarno zdravstveno varstvo; Primary health care; Therapy; zdravljenje